Pengaruh Kualitas Pelayanan dan Komunikasi Interpersonal Terhadap Kepuasan Masyarakat dalam Pelayanan Publik Nagari - Dheva Agustin Adriyan; Boni Saputra (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study analyzes the influence of service quality and interpersonal communication on community satisfaction in the context of public services at the village level. The phenomenon of community satisfaction with public services is a fundamental indicator of the legitimacy of local government. However, the literature cannot integrate technical and relational dimensions in one analytical framework. he study used an associative quantitative approach with an associational design of 305 respondents of the service user community in Nagari Limbanang, Lima Puluh Kota Regency, West Sumatra. Data were collected through a structured questionnaire with a 5-point Likert scale. Data analysis using multiple linear regression with classical assumption testing to ensure model validity. The results showed that service quality positively and significantly affected community satisfaction, as did interpersonal communication. Simultaneously, both variables were able to explain 42.2% of the variability in community satisfaction. The study concluded that a holistic approach that integrates service system improvement with apparatus communication capacity building is optimal for community satisfaction. Practical implications include the need for a comprehensive training policy for nagari officials that emphasizes technical and interpersonal skills in a balanced manner.